Comparative expression of pro-inflammatory and apoptotic biosignatures in chronic HBV-infected patients with and without liver cirrhosis. (December 2021) - Barathan, Muttiah; Riazalhosseini, Behnaz; Iyadorai, Thevambiga; Vellasamy, Kumutha Malar; Vadivelu, Jamuna; Chang, Li-Yen; Zulpa, Ahmad Khusairy; Larsson, Marie; Shankar, Esaki M.; Mohamed, Rosmawati
Abstract: The interplay of immune mediators is paramount to optimal host anti-viral immune responses, especially against chronic hepatitis B virus (HBV) infection. Here, we investigated the dynamic changes in host immune responses in chronic HBV-infected individuals with and without liver cirrhosis by examining the signatures of apoptosis and plasma levels of pro-inflammatory cytokines, chemokines, and cytotoxic proteins. A total of 40 chronic HBV patients with and without liver cirrhosis were studied for plasma levels of immune mediators, and signatures of apoptosis in peripheral blood mononuclear cells (PBMCs). The intracellular concentrations of reactive oxygen species (ROS) in patients with chronic HBV with liver cirrhosis was relatively higher as compared to chronic HBV patients. The onset of apoptosis was sustained due to ongoing liver inflammation in concert with plasma TNF-α and IL-6 levels. Plasma VEGF was upregulated among chronic HBV patients with liver cirrhosis, whereas CCL2, CCL5 and granzyme B levels were down-regulated. High levels of ROS, IL-6 and TNF-α correlated with ongoing inflammation among chronic HBV patients with liver cirrhosis, which likely attributed to the expression of biosignatures of apoptosis and activation in immune cells. Highlights: The intracellular concentrations of reactive oxygen species (ROS) in patients with chronic HBV with liver cirrhosis was relatively higher as compared to chronic HBV patients. The onset of apoptosis was sustained due to ongoing liver inflammation in concert with plasma TNF-α and IL-6 levels. Plasma VEGF was upregulated among chronic HBV patients with liver cirrhosis, whereas CCL2, CCL5 and granzyme B levels were down-regulated. High levels of ROS, IL-6 and TNF-α correlated with ongoing inflammation among chronic HBV patients with liver cirrhosis, which likely attributed to the expression of biosignatures of apoptosis and activation in immune cells.